PEMANFAATAN BENTONIT TERPILAR SEBAGAI KATALIS REAKSI ESTERIFIKASI LANGSUNG SENYAWA TABIR SURYA OKTIL p-METOKSISINAMAT - Subekti Wibowo, ; Maria Monica Sianita, ; Titik Taufikurahmah, (Matematika dan Sains, 2010)
The goal of research were to find percent yield of octyl p-metoxycinnamat (OPMS) obtained from direct esterification between p-metoxycinamic acid and n-octanol using the Zinc pillaring bentonite as catalyst. Zinc pillaring bentonite was made by mixing the bentonite and pillaring agent at 80 oC for 50 menutes. OPMS was prepared by heating p-metoxycinamic acid and n-octanol using zinc pillaring bentonite for 4 hours at 60-70 oC. Structure of OPMS was identified by spectroscopic methods including UV-Vis and IR spectrophotometer, while percent yield was determined using densitometry method. Based on this research, percent yield of OPMS was 42,4196 %.oC for 50 menutes. OPMS was prepared by heating p-metoxycinamic acid and n-octanol using zinc pillaring bentonite for 4 hours at 60-70 oC. Structure of OPMS was identified by spectroscopic methods including UV-Vis and IR spectrophotometer, while percent yield was determined using densitometry method. Based on this research, percent yield of OPMS was 42,4196 %.